Failure of Conservative Treatment in Two Cases of Polyarteritis Nodosa with Superior Mesenteric Artery Involvement Presenting with Abdominal Pain - Ho Chan Sim; Ju Hyoung Lee; Ji Woon Lee; Seung Hyun Park; Ju Won Lee; Heui-Jeong Jeong; Jin Lee; Sung Yeun Yang (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2017)
Polyarteritis nodosa (PAN) is a systemic necrotizing vasculitis affecting medium- or small-sized arteries. Its diagnosis may be delayed because it is a rare disease, and patients presenting with PAN demonstrate variable clinical manifestations and non-specific laboratory abnormalities. Gastrointestinal involvement occurs in 14∼65% of patients with PAN and is a significant cause of morbidity and mortality. Thus, early diagnosis is very important in PAN with gastrointestinal involvement. We report two cases of rapidly progressive PAN presenting with abdominal pain, having failed conservative treatment.